A Leydig Cell Tumour in a Cat: Histological and Immunohistochemical Findings - Pietro Asproni; Francesca Millanta; Davide Lorenzi; Alessandro Poli (Case Reports in Veterinary Medicine)
A 13-year-old intact male cat was submitted to castration after the finding of the enlargement of the right testis during the clinical visit. Macroscopically, a nodule of 2 cm of diameter was observed on the cut surface of the enlarged testis. Histologically, the nodule was composed by polyhedral to elongated cells with a large, eosinophilic, and vacuolated cytoplasm and small, round, and dark nuclei. These cells were arranged in acinar structures and solid sheets. The tumour was diagnosed as a Leydig cell tumour. Immunohistochemical analysis revealed that neoplastic cells were vimentin, calretinin, and melan-A positive, whereas a lack of immunoreactivity to cytokeratins confirmed the diagnosis. To our knowledge, this is the first description of a feline Leydig cells tumour without any concurrent testicular neoplasm or in a nonretained testis.